Radiotracer investigations to study the hydrodynamic characteristics of continuous phase in a pulsed sieve plate extraction column - Din, G.U.; Khan, I.H.; Chughtai, I.R.; Inayat, M.H.; Jin, J.H. (EPJ Web of conferences, 2013)
The present investigations are focused to study the hydrodynamic characteristics of continuous phase in a pulsed sieve plate extraction column using super(68)Ga in the form of gallium chloride from an industrial radionuclide generator ( super(68)Ge/ super(68)Ga). Labeling of water with the subject radiotracer in water-kerosene environment was evaluated. Experiments for Residence Time Distribution (RTD) analysis were carried out for a range of dispersed phase superficial velocities in a liquid-liquid extraction pulsed sieve plate column operating in the emulsion regime with water as continuous and kerosene as dispersed phase. Axial Dispersion Model (ADM) was used to simulate the hydrodynamic characteristics of continuous phase. It has been observed that the axial mixing in the continuous phase decreases and slip velocity increases with increase in superficial velocity of dispersed phase while the holdup of continuous phase was found to decrease with increase in superficial velocity of dispersed phase. ADM with open-open boundary condition was found to be a suitable model for the subject system.